Chapter 4 'She sleeps well and eats an egg': convalescent care in early modern England - Newton, Hannah (Social Histories of Medicine, 2017)
"Very little is known about early modern approaches to convalescence and the author investigates the measures were taken by physicians and laypeople to restore health after illness. Drawing on medical texts, regimens, letters, and diaries, this chapter shows that the treatment of the convalescent differed both from the care of the sick and the healthy. It shows the vital place of the non-naturals in early modern medicine, and the role played by 'Nature', understood as the body's principal agent and governor in physiological processes. The author finds that the 'six non-natural things' were on the one hand used as a way of gauging the extent of recovery, and on the other, were manipulated in a therapeutic role to ensure that both strength and flesh were restored. Thus, any remaining humours which might cause a relapse must be evacuated: good sleep, improved appetite and an ability to exercise were all signs of improvement but each, managed appropriately, also helped to restore strength, whilst negative emotions could endanger recovery and in its place cheerfulness -which was a restorative-must be encouraged."